Personal and Neighborhood Socioeconomic Status and Indices of Neighborhood Walk-ability Predict Body Mass Index in New York City - Rundle, Andrew (2008)
Past research has observed inverse associations between neighborhood and personal level measures of socioeconomic status and body mass index (BMI), but has not assessed how personal and neighborhood level measures might interact together to predict BMI. Using a sample of 13,102 adult residents of New York City who participated in a health survey, cross-sectional multi-level analyses assessed whether personal income, education and Zip code level poverty rates were associated with BMI. Demographic, income, education and objectively measured height and weight data were collected in the survey and poverty rates and the proportion of Black and Hispanic residents in the subject’s Zip code were retrieved from the 2000 Census. Zip code level population density and land use mix, indices of neighborhood walk-ability which are often higher in lower income neighborhoods and are associated with lower BMI, were also measured. After controlling for individual and Zip code level demographic characteristics, increasing income was associated with lower BMI in women but not in men, and college and graduate level education was associated with lower BMI in both men and women. After control for income and individual and Zip code level demographic characteristics, higher Zip code poverty rate was unassociated with BMI. However, as expected, indices of neighborhood walk-ability acted as substantial inverse confounders in the relationship between Zip code poverty rate and BMI. After further adjustment for indices of neighborhood walk-ability, Zip code poverty rate became significantly, and positively associated with BMI in women. Among women, the inverse association between income and BMI was significantly stronger in richer compared to poorer Zip codes. In men and women, the association between college and graduate education and lower BMI was significantly stronger in richer versus poorer Zip codes. These analyses suggest that neighborhood socioeconomic context influences how personal socioeconomic status is measured to influence body size.